Session I: Keynote Panel, Describing the Legal Landscape - Mehta, Probir (The Columbia Journal of Law & the Arts, 2017)
These remarks are a transcript of a talk that was given on October 14, 2016, at the Kernochan Center Annual Symposium at Columbia Law School. Session I, the Keynote Panel of the Symposium, addressed the legal landscape of copyright treatises and free trade agreements, including the role of FTAs and their benefits and disadvantages, and how copyright obligations in FTAs may differ from those in international treaties. Session Panelists: Probir Mehta, Assistant U.S. Trade Representative for Innovation and Intellectual Property Steven J. Metalitz, Partner, Mitchell, Silberberg & Knupp LLP and Counsel to the International Intellectual Property Alliance